Pan-immune-inflammation value is associated with the clinical stage of colorectal cancer - Zhao, HanZheng; Chen, Xingyu; Zhang, WenHui; Cheng, Die; Lu, Yanjie; Wang, Cheng; Li, JunHu; You, LiuPing; Yu, JiaYong; Guo, WenLong; Li, YuHong; Huang, YueNan (Frontiers in Surgery, 2022)
Objective We investigated the clinical significance of preoperative pan-immune-inflammation value (PIV) in patients with colorectal cancer (CRC). Methods In this retrospective study, 366 cases who underwent surgery for CRC were enrolled. Their clinical data were collected. PIV was calculated with the formula PIV = [neutrophil count (109/L)× platelet count (109/L) × monocyte count (109/L) /lymphocyte count (109/L). Patients were divided into high PIV (> median PIV) and low PIV (< median PIV) groups. The relationship between PIV and clinicopathological features of CRC was investigated. Receiver operating characteristic (ROC) curve was plotted to indicate the value of immune-inflammatory biomarkers (IIBs) in predicting the TNM stage of CRC, and the area under the curve (AUC) was calculated to evaluate the actual clinical value of IIBs. AUC > 0.5 and closer to 1 indicated the better predictive efficacy. The influencing factors of PIV in CRC were analyzed. Results We found that PIV was positively correlated with tumor size (r = 0.300, p < 0.05), carcinoembryonic antigen (CEA) (r = 0.214, p < 0.05) and carbohydrate antigen 125 (CA-125) (r = 0.249, p < 0.05), but negatively correlated with albumin (Alb) (r = −0.242, p < 0.05). PIV was significantly different in patients with different tumor locations (left or right), surgical methods (laparotomy versus laparoscopic surgery) (p < 0.05), and patients with different pathological T stages, N-stage and TNM stages (p < 0.05). ROC curve analysis of IIBs showed the AUC of PIV was greater than other markers when combined with CEA or carbohydrate antigen 19–9 (CA19–9). Multivariate regression analysis identified T stage, CEA, Alb, and tumor size as the independent influential factors of PIV in CRC. Conclusion PIV is associated with the tumor stage in patients with CRC, which may be useful in preoperative assessment of CRC.